A theoretical view of 1,3-butadiene selective hydrogenation toward cis-2-butene on PdNi layered catalyst - Gómez, Guillermina (2015)
The production of cis-2-butene (cis-2B) on Pd/Ni(1 1 1) bimetallic model was evaluated considering two possible reactions: through the hydrogenation of 1,3-butadiene (13BD) adsorbed on a cis-geometry site and through the isomerization of trans-2-butene (trans-2B). For that purpose, density functional theory (DFT) calculations were performed following the corresponding Horiuti–Polanyi mechanisms. In the hydrogenation, two competitive pathways produce cis-2B and trans-2B from 13BD species adsorbed on di-π-cis and 1,2,3,4-tetra-σ sites, respectively. The cis-2B is obtained with smaller energy requirements than the trans-2B isomer in spite of the adsorption of 13BD on the di-π-cis site is 0.10 eV less stable than on the 1,2,3,4-tetra-σ site. On the other hand, the trans-2B previously formed could be isomerized to cis-2B, and vice versa, trough the 2-butyl intermediates, but the elevated energetic barriers to hydrogenate/dehydrogenate both 2B isomers would avoid these processes. In fact, the dehydrogenation reaction is the limiting step of the isomerization reaction. From these results, we infer that on the Pd/Ni(1 1 1) surface the cis-2B isomer is easier to be formed via the 13BD hydrogenation on the di-π-cis site than via the trans/cis isomerization of 2B